2016
DOI: 10.1038/srep37114
|View full text |Cite
|
Sign up to set email alerts
|

Cardioprotection by combination of three compounds from ShengMai preparations in mice with myocardial ischemia/reperfusion injury through AMPK activation-mediated mitochondrial fission

Abstract: GRS is a drug combination of three active components including ginsenoside Rb1, ruscogenin and schisandrin. It derived from the well-known TCM formula ShengMai preparations, a widely used traditional Chinese medicine for the treatment of cardiovascular diseases in clinic. The present study explores the cardioprotective effects of GRS on myocardial ischemia/reperfusion (MI/R) injury compared with ShengMai preparations and investigates the underlying mechanisms. GRS treatment significantly attenuated MI/R injury… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 44 publications
0
21
0
Order By: Relevance
“…Aberrant mitochondrial dynamics play critical roles in the pathological processes of ischemic stroke [ 14 ]. Previous studies have shown that YQFM protects against myocardial ischemia/reperfusion injury via AMPK pathway mediated mitochondrial fission [ 39 ] and oxygen-glucose deprivation-induced PC12 cell apoptosis through ER stress [ 36 ]. However, the effects of YQFM against mitochondrial dysfunction and excessive fission induced by ischemic stroke have not been fully elucidated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Aberrant mitochondrial dynamics play critical roles in the pathological processes of ischemic stroke [ 14 ]. Previous studies have shown that YQFM protects against myocardial ischemia/reperfusion injury via AMPK pathway mediated mitochondrial fission [ 39 ] and oxygen-glucose deprivation-induced PC12 cell apoptosis through ER stress [ 36 ]. However, the effects of YQFM against mitochondrial dysfunction and excessive fission induced by ischemic stroke have not been fully elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…YQFM also ameliorates blood-brain barrier (BBB) dysfunction through NF- κ B and ROCK1/MLC signaling pathways [ 37 , 38 ]. More importantly, YQFM is effective in mitigating myocardial ischemia/reperfusion injury by modulating AMPK activation-mediated mitochondrial fission [ 39 ]. However, the effects and potential mechanisms of YQFM on ischemic stroke-induced neuronal mitochondrial fission have not been fully elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…Cardiac left ventricular function and coronary blood flow were assessed non-invasively at 18 h after MIRI using an ultra-high resolution small animal ultrasound Vevo 2100 Imaging System (VisualSonics, Toronto, ON, Canada) equipped with a 30 MHz transducer ( Chen et al, 2016 ; Li et al, 2016 ). The mice were anesthetized using 1.5–2.0% isoflurane in O 2 gas.…”
Section: Methodsmentioning
confidence: 99%
“…17 Previous findings suggest that GRS mitigates myocardial I/R injury by suppressing mitochondria-mediated apoptosis and modulating AMP-activated protein kinase-mediated mitochondrial fission. 18 However, the effects of GRS on ischemic stroke are yet to be characterized.…”
Section: Introductionmentioning
confidence: 99%